Efficacy of a multimodal lifestyle intervention (The Lift Project) for improving the mental health of individuals with an affective mood disorder living in South Africa - Oakes-Cornellissen, Amanda; Morton, Darren; Rankin, Paul; Renfrew, Melanie (Frontiers in Psychology, 2023)
Background: Affective disorders are becoming more pervasive worldwide, including in Southern Africa, where treating patients with these conditions is challenging due to social and financial constraints. A variety of non-pharmacological approaches including lifestyle medicine (e.g., exercise, nutrition, sleep) and positive psychology practices (e.g., gratitude, service), are effective for treating mental health conditions. Methods: Twenty-six individuals from South Africa with a diagnosed mental health condition participated in a ten-week multimodal intervention incorporating a diverse range of non-pharmacological strategies for improving mental health. Mental health metrics were assessed pre-and post-intervention, including general mental health (MH), vitality/energy (VIT), depression, anxiety, stress, and satisfaction with life. MH and VIT were also measured weekly. Results: Improvements were observed in all mental metrics from pre- to post-intervention: MH (59%, p<0.001, Cohen’s D=1.36), VIT (110%, p<0.001, Cohen’s D=1.71), depression (-46%, p<0.001, Cohen’s D=-1.06), anxiety (-48%, p<0.001, Cohen’s D=-1.21), stress (-36%, p<0.001, Cohen’s D=-1.08) and life satisfaction (23%, p<0.001, Cohen’s D=0.66). Significant improvements in MH and VIT were observed after only one week of the intervention and progressively increased until the seventh week, after which further improvements were not statistically significant. Conclusions: The findings of this cohort study indicate that a multimodal intervention that incorporates lifestyle and positive psychology practices may benefit individuals living with an affective disorder. Non-pharmacological, multimodal interventions might offer a cost-effective and stigma-free way of providing mental health promotion and treatment at a population level.